а) (х+4)(х+5)-5≤7

б) 6-(2х+1,5)(4-х)≥0

в)(3х+2)(х-1)+(2х+1)(2х-1)<6х2-х+1

г) (2,5-3х)2-8х2 ≥2,75-15х

1

Ответы и объяснения

2013-04-15T15:50:53+00:00

а) (х+4)(х+5)-5≤7

x+4x+5-5<=7

5x<=-5+5+7

5x<=7

x<=7/5=1,4

 

б) 6-(2х+1,5)(4-х)≥0

6-2x-6-x>=0

-3x>=-6+6

x>=-3

 

в)(3х+2)(х-1)+(2х+1)(2х-1)<6х2-х+1

3x+2x-1+2x+2x-1<6x^2-x+1

-6x^2+3x+2x+2x+2x+x<1+1+1

-6x^2+10x-3<0 |*(-1)

6x^2-10x+3=0

D=(-10)^2-4*6*3=100-72=28

x1=-10+28/12=1,5

x2=-10-28/12=3,16

 

г) (2,5-3х)2-8х2 ≥2,75-15х

5-6x-8x^2>=2,75-15x

-8x^2-6x+15x>=-5+2,75

-8x^2+9x+2,25>=0 |*(-1)

8x^2-9x-2,25

D=(-9)^2-4*8*(-2,25)=81+72=153

x1=9+153/16=10,125

x2=9-153/16=-9